KAJIAN KRITIS TERHADAP PELAPORAN DANA DESA - Alfonsus Jantong; Yakobus Kaditti Bangun (Magister Akuntansi, Universitas Atma Jaya Makassar, 2021)
This study aims to criticize village fund reporting by using qualitative approach. The data used in this study is secondary data in the form of literature related to village fund as well as related research journals. Descriptive analysis method as an analyst tool. The results of the analysis showed that the reporting of village funds in accordance with the regulation of the minister of home affairs number 113 of 2014 concerning the reporting of village funds but not in accordance with the prevailing government accounting standards, other findings indicate a late reporting process, the existence of interfensions in the use and reporting of village funds, obstacles to infrastructure and human resources are lacking. The existence of village funds is very beneficial for the village government in development. Reporting must be consistent with higher regulations, the need for specific reporting for village funds, as well as increased community supervision and participation roles.